Self-Management And Life Quality Of Diabetes Mellitus Patients: A Literature Review - Desi Natalia Trijayanti Idris; Erlin Kurnia; Rahmat Aji Wibowo (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Aim: Diabetes mellitus is a group of metabolic disorders characterized by increased blood glucose levels (hyperglycemia). Diabetic patients must carry out diabetes self-management to prevent complications and to achieve an optimal quality of life.Desain: Study Literature review Methods: Literature obtained from using PubMed, DOAJ, SINTA, and Google Scholar and 10 literature reviews were analyzed by PICO. Results:Research results from the 10 Literature Review obtained statistical test results with results p= 0.00 to p= 0.003 where p<0.05 from Suciana, et al, (2019); Asnaniar and Safruddin (2019); Putri (2019); Luthfa and Fadhilah, (2019); Oktaviani dan Sofiani, (2019); Navicharern (2019)which means that there is a significant relationship between diabetes self-management and the life quality of diabetes mellitus patients. Conclusion: If diabetes self-management is implemented well, the life quality of diabetes mellitus patients will be better.